Reuse of solid waste proceedings of a conference on the practical implications of the reuse of solid waste, organized by the Institution of Civil Engineers, held in London on 11-12 November 1981. (Thomas Telford, 1982)
These papers discuss solid waste as an energy source, agricultural purposes, landfull operations and highlight a way ahead.
Keywords: Recycling (Waste, etc.) -- Great Britain -- Congresses.; Refuse and refuse disposal -- Great Britain -- Congresses.; Refuse as fuel -- Great Britain -- Congresses.; elektronické knihy; electronic books